2012
DOI: 10.1051/hydro/2012050
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study of marine zooplankton communities in the Tangier and M’Diq (Gibraltar strait) regions

Abstract: -This comparative study of mesozooplankton communities in the Tangier (Atlantic) and M'Diq (Mediterranean) regions was carried out in March, May and December 2006 and in May, July and November 2007. In both sectors, the zooplankton is mainly dominated by copepods, which represent 93% in Tangier and 87% in M'Diq, with respectively 85 species in 24 families and 81 divided into 22 families. Spatio-temporal analysis of Copepod specific richness data revealed highest values occurring in both areas during December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 21 publications
0
8
0
Order By: Relevance
“…Similarities (e.g. Madin, 1991;Champalbert, 1996;Xavier & Soest, 2012;Zaafa et al, 2014) and differences (e.g. Triantafyllidis et al, 2005) have been reported between Atlantic and Mediterranean communities for zooplankton and decapods.…”
Section: Spatial and Vertical Variability Of Decapod Communitiesmentioning
confidence: 68%
“…Similarities (e.g. Madin, 1991;Champalbert, 1996;Xavier & Soest, 2012;Zaafa et al, 2014) and differences (e.g. Triantafyllidis et al, 2005) have been reported between Atlantic and Mediterranean communities for zooplankton and decapods.…”
Section: Spatial and Vertical Variability Of Decapod Communitiesmentioning
confidence: 68%
“…Several studies involving zooplankton sampling with mesh sizes ranging from 147 to 200 microns showed the dominance of copepods in different Mediterranean ecosystems greater than 60% in the eastern and western Alboran Sea [57][58][59]. The dominance of copepods was previously demonstrated in the Moroccan Mediterranean [22,30] and in the Moroccan Atlantic coasts [36,37,60,61], as well as in the Canary Current Large Marine Ecosystem (CCLME) region [38]. Although samples were collected in these areas using nets with different mesh sizes, copepod dominance remains significant and consistent across all these zones.…”
Section: Discussionmentioning
confidence: 86%
“…Studies published on the diversity and distribution of zooplankton along the Moroccan Mediterranean coast are very limited [22,29,30]. This coast has yet to be explored when compared with the Atlantic Coast [31][32][33][34][35][36][37][38].…”
Section: Introductionmentioning
confidence: 99%
“…The inflow of Atlantic water, may explain the presence of some rare species (Youssara & Gaudy, 2001;Zaafa et al, 2012). As an example, Centropages chierchiae was recorded only in a few stations.…”
Section: Discussionmentioning
confidence: 99%
“…In the Mediterranean Sea, its distribution is limited to the western part (Razouls et al, 2005(Razouls et al, -2016 influenced by the Atlantic flow. According to 2006-2007 data, among the 103 species recorded at two transects on both sides of the Gibraltar Strait, 61.2% were common in both sectors, whereas 21.4% and 17.5% were endemic to the Atlantic Ocean and the Mediterranean Sea respectively (Zaafa et al, 2012).…”
Section: Discussionmentioning
confidence: 99%